1997
DOI: 10.1007/s002800050598
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase II-dependent cytotoxicity of alkylaminoanthraquinones and their N-oxides

Abstract: We studied the role of DNA topoisomerase II in the biological actions of a series of novel alkylaminoanthraquinones, including N-oxide derivatives designed as prodrugs liable to bioreductive activation in hypoxic tumour cells. Drug structures were based upon the DNA-binding anticancer topoisomerase II poison mitoxantrone with modifications to the alkylamino side chains. The agents included AQ4, 1,4-bis{[2-(dimethylamino)ethyl] amino}5,8-dihydroxy-anthracene-9,10-dione, and AQ6, 1{[2-dimethylamino)-ethyl]amino}… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 14 publications
1
50
0
Order By: Relevance
“…The intercalation is stabilized by electrostatic interactions between the protonated tertiary amino group of the side chain and the phosphate backbone of the DNA. Previous molecular modeling studies have suggested that anthraquinone derivatives substituted at the 1,4-and 1,8-a-NH(CH 2 ) 2 NH(CH 2 CH 3 ) 2 1 side chain intercalate with DNA, with both substituents in the same groove (classical intercalation), while the similarly substituted 1,5-derivative intercalates, in a threading mode, with a side chain in each groove. The current study shows that binding appears to involve a preference for AT-containing sequences in living cells suggested by the results of Hoechst 33342 quenching studies, in which DRAQ5 appears to have the ability to colocate at a significant fraction of Hoechst 33342 binding sites, and to have the potential for minor groove interactions revealed by modeling studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intercalation is stabilized by electrostatic interactions between the protonated tertiary amino group of the side chain and the phosphate backbone of the DNA. Previous molecular modeling studies have suggested that anthraquinone derivatives substituted at the 1,4-and 1,8-a-NH(CH 2 ) 2 NH(CH 2 CH 3 ) 2 1 side chain intercalate with DNA, with both substituents in the same groove (classical intercalation), while the similarly substituted 1,5-derivative intercalates, in a threading mode, with a side chain in each groove. The current study shows that binding appears to involve a preference for AT-containing sequences in living cells suggested by the results of Hoechst 33342 quenching studies, in which DRAQ5 appears to have the ability to colocate at a significant fraction of Hoechst 33342 binding sites, and to have the potential for minor groove interactions revealed by modeling studies.…”
Section: Discussionmentioning
confidence: 99%
“…tein targets for molecular therapeutics, as shown by the anthraquinone-mediated inhibition of DNA topoisomerase II function (2) and the anthracycline-mediated blocking of mismatch repair (3). Critically, both the development of novel drugs with DNA binding properties (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, where reduction was facilitated, potent cytotoxicity was observed in the nM range (Patterson, 1993;Wilson et al, 1996;Smith et al, 1997b). In vitro the differential activity of AQ4N, to its active metabolite AQ4, is considerably greater than any other N-oxide described including DACA-N-oxide and nitracrine N-oxide (Wilson et al, 1996).…”
Section: Tumour Cell and Topoisomerase II Targeting By Aq4nmentioning
confidence: 95%
“…The experiments was carried out as previously described using the anthraquinone-based clinical prodrug AQ4N and its metabolite AQ4 (topo IIα inhibitor) as negative and positive controls respectively [22]. All compounds were shown to completely inhibit topo IIα at 2.5 µM but at lower concentrations a dose-response was observed.…”
Section: Inhibition Of Topo Iiα Activitymentioning
confidence: 99%